Utility of a Mycobacterium leprae molecular viability assay for clinical leprosy: An analysis of cases from the Philippines, Ethiopia, and Nepal - Lenz, Shannon M.; Ray, Nashone A.; Lema, Tsehaynesh; Collins, J. Hunter; Thapa, Ruby; Girma, Selfu; Balagon, Marivic; Bobosha, Kidist; Hagge, Deanna A.; Williams, Diana L.; Scollard, David M.; Lahiri, Ramanuj; et al. (Frontiers in Tropical Diseases, 2022)
Mycobacterium leprae is a slow-growing species of mycobacteria that cannot be cultured in axenic media. This presents a number of challenges for monitoring treatment efficacy and advancing new drugs and regimens for treating leprosy. We previously developed a molecular viability assay (MVA) which measures expression of hsp18 and esxA transcripts to determine viability of M. leprae directly from infected tissue. The objective of the current study was to determine the utility of the MVA for practical use on clinical specimens. Leprosy cases from the Philippines (N = 199), Ethiopia (N = 40), and Nepal (N = 200) were diagnosed by clinical examination, slit-skin smears (SSS) from index sites, and/or histopathology. Biopsy specimens for MVA were collected from an active lesion and stored in 70% ethanol. DNA and RNA were extracted from the tissue, and M. leprae were enumerated on the DNA fraction via RLEP qPCR. Based on this count, DNased RNA was normalized to the equivalent of 3x103 M. leprae per reverse transcription reaction, and hsp18 and esxA transcripts were amplified by PCR on the resulting cDNA. There was a strong correlation between RLEP enumeration on the specific biopsy specimen for MVA and the average SSS bacterial index (BI) in all three cohorts (p < 0.001). The MVA could be performed on most biopsies with an average SSS BI ≥ 2 and showed a decrease in M. leprae viability with increasing duration of leprosy multidrug therapy (R2 = 0.81; p ≥ 0.001). The MVA also detected viable M. leprae in relapse patients where it showed significant correlation with the mouse footpad assay (p = 0.018). The MVA is a M. leprae-specific, sensitive, and relatively quick test. Clinically, the MVA would likely be most useful to monitor treatment, confirm suspected relapse cases, and determine efficacy of new leprosy drugs in clinical trials.